Pulmonary Hypertension: Understanding the Underlying Anatomy and Physiology of Pulmonary Circulation - Amien, Bagus Radityo; Putra, Andika Chandra (Jurnal Respirologi Indonesia, 2025)
The circulatory system has a vital role in fulfilling oxygen demand in tissues and maintaining homeostasis. There are two types of circulatory systems in our body, the systemic and pulmonary circulation. Pulmonary circulation, the critical pathway of blood oxygenation through heart-lung-pulmonary vascular interaction, remains poorly understood despite its central role in the various pulmonary vascular diseases. One of the most prevalent pulmonary vascular diseases is pulmonary hypertension (PH), which is characterized by high mortality and disease progression. A thorough understanding of the physiologic structure and function of pulmonary circulation is essential for diagnosing and treating patients with PH.  Pulmonary blood flow is determined by pulmonary vascular pressure (PVP) and pulmonary vascular resistance (PVR). Lung volume, neural factors (sympathetic and parasympathetic nervous systems), humoral factors (vasoconstrictor and vasodilator), and alveolar hypoxia play an important role in regulating PVR. Alveolar hypoxia triggers hypoxic pulmonary vasoconstriction to maintain the ventilation-perfusion ratio balance. High PVR increases pulmonary arterial pressure (Pa), which is the main pathophysiology of PH. In addition, endothelial dysfunction and vasoactive imbalance also contribute significantly to the pathogenesis of the disease.